Análise farmacológica e legal de prescrições odontológicas de antibióticos: um estudo transversal - Sheila Silva Monteiro Lodder Lisboa (2015)
Dentists have the prerogative to prescribe drugs as adjuncts to dental treatment (BRASIL, 1966). In 2011, with the enactment of the Collegiate Board Resolution no.20 of the National Health Surveillance Agency - ANVISA, antibiotics became drugs subject to special prescription. This descriptive cross-sectional study aimed to know the limitation act of dentists as to antibiotics, identify the most prescribed, determine if there was an error in meeting the legal requirements and identify errors in prophylactic prescription. Dental antibiotic prescriptions filled in the largest drugstore chain in Belo Horizonte, Minas Gerais were analyzed from 1 July 2011 to 30 June 2012. In the period of data collection there were 75 stores in operation. It was possible to retrieve information about the prescriptions of 69 of them (return rate = 92%). For the study of 31,105 prescriptions, there was a draw of the sample, with calculation based on estimated proportions (50% of estimated proportion with prescription error, 5% precision and 95% of confidence level). 434 prescriptions were selected by the simple random sampling technique. After excluding those with repeating prescriber and / or patient, 366 prescriptions were analyzed. The accuracy recalculated for this amount was equal to 5.09%. After double entry in Epi-Date program it was created a database in the SPSS software. The research was subjected and approved by the Ethics Committee of UFMG. The results of analysis showed that most prescribed antibiotics belong to the group of penicillins (71.9%) and macrolides (17.6%). Also were prescribed, to a lesser extent, antibiotics for topical application and several others, including antifungal, in addition to associations: amoxicillin with ciprofloxacin and clindamycin. In 27.9% of the prescriptions there were errors in spelling or disobedience to the determination to follow the Brazilian Common Denomination (DCB). Dose errors, timing, and duration of treatment have been identified respectively in 24.6%, 29.2% and 42.9% of prescriptions. More than half (53.8%) of dentists did not register the dosage form in the prescription, or registered in abbreviated form, while the others did the complete way: capsules, tablets. Most of them did not show how to use (97.3%) and patient identification data, especially sex, age and address were absent. Of the 366 selected prescriptions, 91 corresponded to the prophylactic use. The generic name was spelled incorrectly on 21 and the dose was lower than that recommended in 72 of them. On most prescriptions for prophylactic use (79.1%) there was error duration of antibiotic therapy, with 71 guidelines for continuity of use after the initial dose. It is concluded that dentists make mistakes in prescribing in both the legal and pharmacological aspect, contributing to an increase in the cost of treatment, increased risk of side effects and selection of bacterial strains resistant to antibiotics. Prescriptive errors can be avoided with improvements in education, both in graduation and in post-graduation.